PERSONAL HYGIENE, SANITATION AND FOOD SAFETY KNOWLEDGE OF FOOD WORKERS AT THE UNIVERSITY CANTEEN IN INDONESIA - Rahman, Abdul; Tosepu, Ramadhan; Karimuna, Siti Rabbani; Yusran, Sartiah; Zainuddin, Asnia; Junaid, Junaid (Public Health of Indonesia, 2018)
Background: Food and beverage sanitation hygiene is a prevention effort that focuses on activities or actions that are necessary to free food and drinks from hazards that can interfere with or damage health.Objective: This study aimed to identify personal hygiene, sanitation and food safety knowledge of food workers at the canteen university.Methods: This was a descriptive study with observational approach. Thirty-four canteens were recruited using total sampling. Data were analyzed using descriptive statistics with percentage.Results: Findings showed that 11 canteens (32.3%) did not meet the standard for canteen sanitation, 24 canteens (70.6%) did not meet lighting standard, 29 (85.3%) did not meet ventilation standard, 18 (52,9%) did not meet the standard of clean water, 31 (91.2%) did not meet wastewater disposal standard, 23 (67.6%) did not meet the hand washing facility standard, 25 (73.5%) did not meet standard of waste disposal conditions, 28 respondents (85.3%) had good personal hygiene, 6 respondents (14.6%) had poor personal hygiene and all food workers had good knowledge on food safety (100%).Conclusion: Personal hygiene, sanitation and food safety at the university canteen must be carried out continuously. Our findings can be used as a basis for creating healthy university canteen.